Public sector auditing : practical techniques for an integrated approach - Jones, P. C. (Chapman and Hall, 1994)
This book is about: The audit environment and current issues; The essential audit process; Strategic and business planning; Planning the assignment; Controlling and recording the assignment; Audit evidence and the systems-based approach...